Genomic analysis of a nontoxigenic, invasive Corynebacterium diphtheriae strain from Brazil - Encinas, Fernando (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Genética Molecular de Microrganismos. Rio de Janeiro, RJ, Brasil.